The Study of Code-Switching in Nadiatilem’s TikTok Content - Fahmi Aulia Azzahra (Fakultas Ilmu Budaya, 2025)
This study focuses on the analysis of code-switching used in Nadiatilem’s TikTok content. There are two main focuses discussed in this research. The first is the classification of code-switching types. The second is the analysis of the reasons why Nadiatilem uses code-switching in her TikTok content. The theoretical framework by Poplack (1980) is used to classify the types of code-switching, while the framework by Holmes and Nick (2022) is applied to analyze the reasons for code-switching. This research is a qualitative research since the data are non-numeric, utterances. This research employs the documentary technique to collect the data, specifically in the form of Nadiatilem's utterances which consist of code-switching in her TikTok content. Three videos were analyzed, which were uploaded on December 21, 2022, March 28, 2023, and May 27, 2023. A total of 17 utterances containing code-switching were identified as data. This study is also supported by several contributing factors, including the results of a Q&A session during her TikTok live and her personal experiences.
Reuploud Repository hasyim Juni 2026 Validasi file repositori 4 Juni 2026_Dea_Firli
Keywords: Study of Code-Switching; TikTok Content